Why The Big 4 Are Leaders In The Audit Market? A Literature Review - Toscano Moctezuma, Juan Alfonso; Benau, Maria Antonia García (Archives of Business Research, 2017)
The leadership of the large audit firms has generated great interest in the accounting doctrine to explain about the concentration factors of the audit market. The objective of this paper was to make an extensive review about the empirical studies published in the international literature about the reasons why the Big 4 are leaders in the audit market. The methodology used to review the literature contains an important theoretical background, since it is based on a thorough documentary review of the most relevant theoretical and conceptual approaches of international literature. The results indicate that the leadership of the Big 4 in the audit market is due to factors such as; the concentration of the market, the specialization of the audit service by sector and size of the companies audited, the economies of scale, the structured audit methodologies, the demand for the audit service with differentiated quality and the demand of an auditor with reputation.